2020
DOI: 10.3390/ijerph17176354
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Positive Emotion and Interpersonal Relationships to Adaptation of School Life on High School Athletic Class Students

Abstract: Background: Adaption for school life is important for all students. As for athletic students, since they need to cope with schoolwork and extensive training, adaption for school life could be very challenging. Taking this into consideration, the purpose of this study was to explore the factors which may help high school athletic students’ adaption of school life. Owing to this, the study explored previous researches and proposed four hypotheses: the first two hypotheses proposed that athletes’ positive emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…School adaptation generally refers to the degree to which students’ interactions with various features of the school environment enhance their comfort and success ( Ladd et al., 1997 ). The quality of students’ interpersonal relationships within this environment is a particularly important feature that has been shown to positively predict students’ adaptation of school life ( Chang et al., 2020 ; Song, 2017 ; Zeng et al., 2010 ). However, little is known about the mechanisms associated with this relationship in the epidemic control context.…”
Section: Introductionmentioning
confidence: 99%
“…School adaptation generally refers to the degree to which students’ interactions with various features of the school environment enhance their comfort and success ( Ladd et al., 1997 ). The quality of students’ interpersonal relationships within this environment is a particularly important feature that has been shown to positively predict students’ adaptation of school life ( Chang et al., 2020 ; Song, 2017 ; Zeng et al., 2010 ). However, little is known about the mechanisms associated with this relationship in the epidemic control context.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that positive emotions can increase adrenaline in the blood, the hormone that mobilizes the power of the organism, thereby making the person more empowered to achieve their goals [ 18 , 19 ]. Positive emotions are an important condition and marker for maintaining mental health [ 20 ].…”
Section: Basic Theory and Research Methodsmentioning
confidence: 99%
“…The suggested approach to measure adaptability in this paper is based on the total of positivity gain. The reason behind utilizing positivity as the main factor to measure adaptability level of Iraqi students toward E-learning is that positivity has significant impact on student's adaptation to school life [21]. In addition, empirical studies and researches showed that adaptation is rapid and surely complete in response to positive experiences [22].…”
Section: Measurement Of Adaptability Levelmentioning
confidence: 99%